Principles and Practice of Engineering Exam Pass Rate by Gender. Issue 2 (2nd September 2018) - Keen, Julia; Salvatorelli, Anna
ABSTRACT: In many disciplines of engineering, the professional engineering license is an important credential for career advancement. To attain an engineering license, one must pass the Principle and Practice of Engineering (PE) exam after a set amount of time in practice (defined by the state granting the license). While the national pass rate for the exam is available to the public, pass rates based on gender is not collected as most states do not track this demographic. The purpose of this study is to determine the PE exam pass rates for men and women. Pass rate information by gender was requested from each state's licensing board. When gender information was not available, a list of all individuals who sat for the exam and their results were requested. From this list, gender was assigned based on individual names and a pass rate by gender was determined. These data enable a conclusion to be drawn as to whether women are passing the PE exam at a similar rate as men.